Analisis Desain Gedung Whiz Hotel Metode Sistem Rangka Pemikul Momen Khusus - nadeak, lexono x; Suyadi, Suyadi; Widyawati, Ratna (Universitas Lampung, 2016)
AbstractSpecial Moment Resisting Frame System(SMRFS) is a system with the highest ductility and that has detail requirements in the calculation of structural reinforcement components of axial, bending and shear of beam and columns elements, as well as provisions regarding the beam column connection that will affect the overall performance building when receiving earthquake load. This study aims to determine the detail requirements of special moment resisting frame system in accordance with SNI 2847-2013 and performance evaluation of structures with pushover analysis. Based on study results, the level of structure performance in accordance with the performance point obtained shows that the values of the displacement target are 0.042 m in x-direction and 0.413 m in y-direction. The value of the performance point also shows that the building is designed in the Immediate Occupancy condition that is while the building receives the earthquake load, it is expected that the structure will not be damaged. Distribution of plastic hinge is appropriate to the expectation that is the strong column and the weak beam because plastic hinge formation begins from the beam element then the column element. From the pushover analysis, it is obtained the value of the actual reduction factors (R) are 8.9 in x-direction and 7.8 in y-direction, while the values of the actual system over strength factor (Ωo) are 4.34 in x-direction and 5.70 in y-direction and the values of actual deflection magnification factor (Rd) are 5.9 in x-direction and 5.2 in y-direction.Keywords : pavement distress types, severity level, PCIAbstrakSistem Rangka Pemikul Momen Khusus (SRPMK) merupakan sistem dengan daktilitas tertinggi dan memiliki persyaratan yang detail dalam perhitungan penulangan komponen struktur aksial, lentur dan geser untuk elemen balok dan kolom, serta ketentuan mengenai hubungan balok kolom yang akan mempengaruhi kinerja bangunan secara keseluruhan ketika menerima beban gempa. Penelitian ini bertujuan untuk mengetahui detail persyaratan sistem rangka pemikul momen khusus sesuai dengan SNI 2847-2013 dan evaluasi kinerja struktur dengan pushover analysis. Berdasarkan hasil studi, level kinerja struktur sesuai dengan titik kinerja yang didapat menunjukkan nilai dari target perpindahan untuk arah x sebesar 0,042 m dan arah y sebesar 0,413 m. Nilai dari titik kinerja juga menunjukkan bahwa bangunan yang di desain berada pada kondisi Immediate Occupancy dimana kondisi gedung saat menerima beban gempa diharapkan struktur tidak akan mengalami kerusakan. Distribusi sendi plastis sesuai yang diharapkan yaitu kolom kuat dan balok lemah karena terbentuknya sendi plastis diawali dari elemen balok terlebih dahulu kemudian diikuti elemen kolom. Dari hasil analisis pushover didapat nilai faktor reduksi gempa (R) aktual arah x sebesar 8,9 dan arah y sebesar 7,8, sedangkan nilai faktor kuat lebih sistem (Ωo) aktual arah x sebesar 4,34 dan arah y sebesar 5,70 dan nilai faktor pembesaran defleksi (Rd) aktual arah x sebesar 5,9 dan arah y sebesar 5,2.Kata kunci : SRPMK, titik kinerja, sendi plastis, analisis pushover